Responsibility for failures of government: The problem of many hands - Thompson, Dennis F. (2014)
The problem of many hands-the difficulty of assigning responsibility in organizations in which many different individuals contribute to decisions and policies-stands in the way of investigating and correcting the failure of government. The problem can be mitigated by giving greater attention to the design of processes of organizational responsibility. An independent investigation can identify both the individual actions and the structural defects that contributed to an organizational failure. Then, specific individuals can be designated as overseers, who are held responsible for monitoring the structure and making changes as necessary. Three cases-the official responses to terrorist attack on the World Trade Center in 2001, the Deepwater Horizon oil spill in 2010, and the financial crisis that began in 2007-illustrate how this prospective approach of designing responsibility could work in practice. - Reproduced.
Keywords: Public administration